Discoordination and miscoordination caused by sunspots in the laboratory - Jan Siebert; Guanzhong Yang (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
This paper combines two strands of the experimental sunspot literature. It extends the rare literature that focuses experimentally on the coordination problems caused by sunspot variables. It also extends the literature that focuses on coordination games that have a payoff-dominant and a divergent risk-dominant equilibrium. To achieve this, we use a repeated three-player stag hunt game with fixed groups. In our experiment, a sunspot variable points randomly at the risk-dominant or the payoff-dominant choice. We find out-of-equilibrium behavior (discoordination) caused by the sunspot variable in the short run. In the long run, the sunspot variable can lead to coordination of the payoff-dominated equilibrium (miscoordination). If the sunspot-generating process points more frequently to the risk-dominant choice, some groups converge to the sunspot equilibrium.
Keywords: C92; C72; D81; E40; J52; 330; sunspot; coordination